(untitled) (Vietnam Journal of Community Medicine, 2026)
Root canal treatment techniques have been enhanced by advanced technologies, with diode laser standing out for its effectiveness. However, its role in disinfection remains debated. Objectives: To evaluate the effectiveness of root canal treatment for first and second molars with diode laser assistance in canal preparation. Method: A controlled clinical trial with 40 patients randomly divided into two groups. Results: Traditional treatment group: after 1 week, 85% good, 15% average, 0% poor; after 3-9 months, 60% good, 40% average, 0% poor. Diode laser treatment group: after 1 week, 95% good, 5% average, 0% poor; after 3-9 months, 85% good, 15% average, 0% poor. No significant difference between groups after 3-9 months. Conclusion: The diode laser group showed higher success rates, 95% after 1 week and 85% after 3-9 months, compared to the traditional method with 85% after 1 week and 60% after 3-9 months.